Rediscovery and Lectotypification of Eugenia argentea Bedd. (Myrtaceae) An Endemic and Endangered Species of India - Kumar, S.; Shareef, S. M.; Roy, P. E. (Journal of Scientific Research, 2010)
Eugenia argentea Bedd. has been rediscovered from Wayanadu forests in Kerala after a lapse of 138 years of its first collection. Detailed description, photographs, lectotypification, etc are provided. Keywords: Eugenia argentea; Rediscovery; Western Ghat; Lectotypification. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.6210 J. Sci. Res. 3 (1), 213-216 (2011)